Analysing UTAUT with trust toward mobile banking adoption in China and Pakistan: extending with the effect of power distance and uncertainty avoidance. (13th September 2019) - Akhtar, Sadia; Irfan, Muhammad; Kanwal, Shamsa; Pitafi, Abdul Hameed
Banking technology supports financial systems through emerging a solid connection between local population and financial intuitions. Technology acceptance studies with innovative models are considering the key research in Asian countries specifically China and Pakistan. The current study used unified theory of acceptance and use of technology (UTAUT) model with trust factor by moderating two cultural dimensions namely power distance and uncertainty avoidance. In addition, novel ideas were incorporated in determinants to investigate the national cultural effects on individuals' behavioural intentions toward mobile banking adoption in China and Pakistan. Empirical study was performed to test the proposed cross-cultural model using the data obtained from both countries. The model was analysed through multiple and moderated regression analyses using IBM SPSS software. Results proved that performance expectancy, effort expectancy, social influence and trust were important predictors of behavioural intentions to adopt m-banking in Pakistan. On the other hand, performance expectancy and trust have significant effect on individual's behavioural intentions to adopt m-banking in China. Moreover, power distance and uncertainty avoidance were significant moderators in analysing the behavioural intention to use m-banking.